The role of catastrophizing and basic psychological needs satisfaction on health-related quality of life and pain in patients with lumbar disc herniation - Ionescu, Daniela; Iacob, Claudia Iuliana; Brehar, Felix Mircea; Avram, Eugen (Frontiers in Psychology, 2023)
Introduction: Lumbar disc herniation (LDH) is one of the most common conditions associated with functional disability, affecting patients' quality of life (QOL). Disability can be affected by cognitive factors, such as pain catastrophizing. Similarly, unfulfilled basic psychological needs (i.e., autonomy, competence, relatedness) are associated with biases in pain perception and QOL. Using the fear-avoidance model and the self-determination theory, this study investigates (1) the separate contribution of pain-related variables and basic psychological needs satisfaction in predicting QOL in patients proposed for LDH surgery; (2) pre- and post-surgical differences in pain catastrophizing and basic psychological needs satisfaction. Methods: First, we used hierarchical regression on 193 patients (Mage = 46.10, SDage = 11.40) to identify predictors of QOL. Second, we performed paired t-tests on 55 patients to investigate pre- and post-surgical differences in pain catastrophizing and basic psychological needs satisfaction. Results: Hierarchical regression showed that the model predicts 27% of the variance in QOL; medium pain level, age, pain catastrophizing, and basic psychological needs satisfaction were significant predictors. Also, pain catastrophizing significantly decreased after surgery (t(54) = 6.07, p < .001, Cohen's d = .81), but basic psychological needs satisfaction did not modify significantly. Discussion: This research confirms the importance of pain perception and pain catastrophizing for LDH patients’ QOL and broadens the applicability of the self-determination theory for spinal patients.